Systematic Literature Review: Pengaruh Model Pembelajaran Problem Based Learning Terhadap Motivasi dan Hasil Belajar Siswa - Dwi Jayanti; Satinem; Supriyanto (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to systematically synthesize findings from various studies on the effect of Problem Based Learning (PBL) on students’ motivation and learning outcomes. The method used is Systematic Literature Review (SLR), which includes identification of relevant literature, selection of studies based on inclusion and exclusion criteria, data analysis from previous studies, and synthesis of findings to draw comprehensive conclusions. The results indicate that PBL predominantly has a positive and significant effect on students’ motivation and learning outcomes. The most commonly used research method is quasi-experiment with a posttest only control group design, while the most frequently studied subjects and educational levels are Social Studies (IPS) at the junior high school level (SMP/MTs). In conclusion, this study recommends conducting further research with greater variation in methods, subjects, and educational levels that have been minimally explored.  Keywords: Problem Based Learning, Learning Outcomes, Motivation